Elements of Genus Ficus (Moraceae) and other Taxa Vis-a-vis Hydro-edaphic Properties of Woodland Habitat of Nilgiri Biosphere Reserve, Kerala - Singh, J. N. (Indian Forester, 2009)
The present investigation deals with the hydro-edaphic properties and their mutual interaction in the woodland habitat of NBR - Kerala and the ameliorative role of the elements of genus Ficus and other taxa in the in-situ environment of the area. It is held from the results that edaphic factors contain sufficient energy to hold the vegetation / flora of the region in the present form. However, it is a declined status in comparison to 1982 values. Due to presence of appropriate quantum of energy materials in the soils systems, their other related properties like soil-proteins, cation exchange capacity, exchangeable calcium, water holding capacity, porosity, etc. are excellent and system is quite balanced at present. The equally potent agent i.e. waters of the region are quite bereft of dissolved minerals in their per unit volume but totally free of alkali hazards. However, the soil-water interaction is a matter of concern for the region. The chemically dilute waters eat up the mineral riches of the soils and mineral transfer from edaphic media to aqua media is directly proportional to the degree of dilution and periodic length of submergence. Besides, the interactions further create a phenomenal change in the pH environment of edaphic media and strain the system to salt imbalance in the process. In presence of prevalent biotic and abiotic factors of the region the role of the elements of genus Ficus particularly their root systems and leaf litter on soil conditions along with their chief associates observed to be very positive in keeping the system viable and sustainable.